Nexus narratives and resource insecurities in the Mekong Region - Lebel L. (2017)
© 2017 Elsevier Ltd. Several global narratives around resource insecurities have reached the Mekong Region. In the latest reincarnation, experts, bureaucrats and businesses have called for greater attention to a water-energy-food nexus. It is not clear however, if they are talking about the same thing, with the same purpose or that decision-makers are listening. The purpose of this study was to identify the key features of nexus narratives globally, and then analyze how they are being used in the Mekong Region. We used the Narrative Policy Framework to explore narrative content and strategies, and Cultural Theory to help identify policy beliefs of competing coalitions in a mixed-methods analysis. Increasing resource scarcity, which undermines security, was a shared setting in all nexus narratives. Individualist and Hierarchist narratives tend to de-politicize the nexus by promising solutions from innovative businesses and free markets, or through technocratic and managerial control of resources and the environment by bureaucrats. Egalitarian narratives identify victims and villains to re-politicize the nexus around themes of justice and human security. Nexus narratives were used to support and oppose hydropower, irrigation and biofuel development, with Individualist narratives consistently being the most pro-development. Nexus narratives have been widely adopted by international organizations and foreign experts working in the Mekong Region; however, with a few exceptions, they have as of yet had little direct influence on national policy or plans. Several possible reasons are discussed, including limitations of the concept itself.